2020
DOI: 10.1021/acs.orglett.0c03442
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Regulated Coupling of 2-Alkynylbenzaldehydes with Cyclic Amines: Selective Synthesis of Fused N-Heterocycles and Functionalized Naphthalene Derivatives

Abstract: An efficient synthesis of 1,2,3,4-tetrahydrobenzo­[g]­quinoline derivatives through PdCl2-catalyzed, TBHP-promoted, and toluene-mediated dehydrogenation/[4+2] cycloaddition of saturated cyclic amines with 2-alkynylbenzaldehydes was developed. On the contrary, when the reaction medium was changed from toluene to DMSO/H2O, another class of important compounds, naphthyl chain amines, formed via a dehydrogenation–intermolecular condensation–C–N bond cleavage–intramolecular condensation pathway, was obtained with g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 44 publications
(19 reference statements)
0
10
0
Order By: Relevance
“…Alternatively, if the reactive oxocarbenium ion can be trapped by introduction of an appropriate nucleophile, such as H 2 O, tetrahydronaphthols might be accessed after ring-opening of the in situ generated cyclic hemiacetal. Dienamine catalysis can generate electron-rich olefins and has shown a high degree of stereocontrol in cycloadditions and good compatibility with water .…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, if the reactive oxocarbenium ion can be trapped by introduction of an appropriate nucleophile, such as H 2 O, tetrahydronaphthols might be accessed after ring-opening of the in situ generated cyclic hemiacetal. Dienamine catalysis can generate electron-rich olefins and has shown a high degree of stereocontrol in cycloadditions and good compatibility with water .…”
Section: Introductionmentioning
confidence: 99%
“…(Scheme 1a, down). 7 In 2018, Sarpong et al reported a deconstructive strategy for transforming saturated cyclic amines into acyclic haloamines using silver with an oxidantcontaining halogen group as reagents. 8 To eliminate the use of transition metals and oxidants, difluorocarbene reagents have been used for the C−N bond cleavage of cyclic amines to access the multifaceted acyclic architectures under mild conditions.…”
mentioning
confidence: 99%
“…8 Our group developed a PdCl 2 -catalyzed, TBHPpromoted, and toluene-mediated reaction to form α,βdifunctionalized azaheterocycles through the dehydrogenation/[4 + 2] cycloaddition of saturated N-heterocycles with 2-alkynylbenzaldehydes. 9 Recently, Seidel's group achieved α,β-disubstituted or α,β,α′-trisubstituted amines through hydride transfer reactions of N-lithiated amines with a ketone oxidant. 10 Meanwhile, it was noticed that these elegant methods generally furnished functionalized amines with a nucleophilic substituent introduced at the α-site and an electrophilic substituent introduced at the β-site via enamines or endocyclic 1-aza allyl anions as intermediates (Scheme 1A).…”
mentioning
confidence: 99%
“…Xu’s group reported an efficient visible-light-photocatalyzed dehydrogenation/[2 + 2] cycloaddition sequence for the functionalization of dual C­(sp 3 )–H bonds in saturated cyclic amines . Our group developed a PdCl 2 -catalyzed, TBHP-promoted, and toluene-mediated reaction to form α,β-difunctionalized azaheterocycles through the dehydrogenation/[4 + 2] cycloaddition of saturated N -heterocycles with 2-alkynylbenzaldehydes . Recently, Seidel’s group achieved α,β-disubstituted or α,β,α′-trisubstituted amines through hydride transfer reactions of N -lithiated amines with a ketone oxidant .…”
mentioning
confidence: 99%
See 1 more Smart Citation